(untitled) (Medical Forum Monthly, 2020)
Objective: To assess the alterations in the serum lipoproteins in primiparous females suffering from eclampsia and its comparison with the normal healthy female pregnancy. Study Design: Observational / analytical study. Place and Duration of Study: This study was conducted at the Department of Gynaecology, Teaching Hospital Ghazi Khan Medical College, Dera Ghazi Khan from January 2019 to September 2019. Materials and Methods: This transverse research work carried out on 50 primiparous patients of eclampsia and 15 pregnant females with normal blood pressure. The record of the history of every female was maintained on questionnaire. Utilization of standard methods carried out for the measurement of the blood pressure. We collected a blood sample of 5 milliliter from every participant to examine the level of serum lipoproteins. Results: Average age of hypertensive females was 20.18±0.50 years whereas average age of the healthy controls was 21.80±1.14 years. We found a significant difference in the level of lipoproteins. Women present with eclampsia had 26.70%, 27.40%, 29.0%,30.80% and 63.20% high low density lipoprotein cholesterol, triglycerides, ratio between total cholesterol and high density lipoprotein cholesterol, ratio of low density lipoprotein cholesterol to high density lipoprotein cholesterol and ratio of triglycerides and high density lipoprotein cholesterol correspondingly as compared to the group of healthy controls. The concentrations of high density lipoprotein cholesterol, ratio between high density lipoprotein cholesterol and low density lipoprotein cholesterol and level of apolipoprotein A-1 were 24.80%, 54.50% and 25.80% respectively, less in the group of patients as compared to the group of healthy controls. Conclusion: The assessment of the concentration of serum lipoprotein in the duration of antenatal period can be beneficial in early identification and prevention of the development of eclampsia.